Interleukin-1 receptor antagonist ameliorates the pain hypersensitivity, spinal inflammation and oxidative stress induced by systemic lipopolysaccharide in neonatal rats. (May 2020) - Hsieh, Cheng-Ta; Lee, Yih-Jing; Lee, Jonathan W.; Lu, Silu; Tucci, Michelle A.; Dai, Xiaoli; Ojeda, Norma Beatriz; Lee, Hyun Joon; Fan, Lir-Wan; Tien, Lu-Tai
Abstract: Perinatal inflammation-induced reduction in pain threshold may alter pain sensitivity to hyperalgesia or allodynia which may persist into adulthood. In this study, we investigated the anti-inflammatory protective effect of interleukin-1 receptor antagonist (IL-1ra), an anti-inflammatory cytokine, on systemic lipopolysaccharide (LPS)-induced spinal cord inflammation and oxidative stress, thermal hyperalgesia, and mechanical allodynia in neonatal rats. Intraperitoneal (i.p.) injection of LPS (2 mg/kg) or sterile saline was performed in postnatal day 5 (P5) rat pups, and IL-1ra (100 mg/kg) or saline was administered (i.p.) 5 min after LPS injection. Pain reflex behavior, spinal cord inflammation and oxidative stress were examined 24 h after LPS administration. Systemic LPS exposure led to a reduction of tactile threshold in the von Frey filament tests (mechanical allodynia) and pain response latency in the tail-flick test (thermal hyperalgesia) of P6 neonatal rats. Spinal cord inflammation was indicated by the increased numbers of activated glial cells including microglia (Iba1+) and astrocytes (GFAP+), and elevated levels of pro-inflammatory cytokine interleukin-1β (IL-1β), cyclooxygenase-2 (COX-2), and prostaglandin E2 (PGE2) 24 h after LPS treatment. LPS treatment induced spinal oxidative stress as evidenced by the increase in thiobarbituric acid reactive substances (TBARS) content in the spinal cord. LPS exposure also led to a significant increase in oligodendrocyte lineage population (Olig2+) and mature oligodendrocyte cells (APC+) in the neonatal rat spinal cord. IL-1ra treatment significantly reduced LPS-induced effects including hyperalgesia, allodynia, the increased number of activated microglia, astrocytes and oligodendrocytes, and elevated levels of IL-1β, COX-2, PGE2, and lipid peroxidation (TBARS) in the neonatal rat spinal cord. These data suggest that IL-1ra provides a protective effect against the development of pain hypersensitivity, spinal cord inflammation and oxidative stress in the neonatal rats following LPS exposure, which may be associated with the blockade of LPS-induced pro-inflammatory cytokine IL-1β. Highlights: IL1-ra attenuates LPS-induced pain sensitivity in neonatal rats. IL1-ra attenuates LPS-induced spinal cord oxidative stress in neonatal rats. IL1-ra protects against LPS-induced spinal cord inflammation in neonatal rats.